Effects of TiO2 nanoparticles on morphological characteristics of chickpea (Cicer arietinum L.) under drought stress - Roya Ghorbani; Ali Movafeghi; Ali Gangeali; Jafar Nabati (تنش های محیطی در علوم زراعی, 2021)
Introduction Drought stress is one of the most important environmental stresses affecting plant growth and yield. Chickpeas are drought tolerant plant, but drought as a limiting factor affects their yield. Drought stress in chickpeas reduces the length of flowering period and decrees the growth period. There are various strategies for mitigating drought stress, in which nanotechnology has received special attention in plant sciences in recent years. The use of nanoparticles in various plant species indicates their positive effects on plant growth and development. Nanoparticles are atomic or molecular assemblies with dimensions of 1-100 nanometers. Highly permeable nanoparticles increase the water uptake of nutrients and ultimately improve growth. The use of nanoparticles can be effective as a way to mitigate the effects of drought stress. Materials and methods The experiment was carried out as a factorial experiment with three replications in a completely randomized design in a greenhouse. The morphological and physiological characteristics of the plant were assessed at different levels (40, 60 and 90 percentage) of field capacity (FC). FC was measured by calculating the amount of soil humidity. The titanium dioxide nanoparticles (TiO2-NPs) are used in five concentration including 0, 5, 20, 10 and 40 mg/L. Firstly characteristics of nanoparticles were investigated by measuring zeta potential, XRD and TEM. Secondly, a 100 mg/l mother solution was prepared in deionized water. TiO2-NPs were dispersed by ultrasonic bath for 40 min before spraying the solution on the plants. The plants completely were soaked by sprayed solution 4 times each 14 days .Finally after the growth duration some morphological and physiological parameters were measured. The data were analyzed using ANOVA with Statistical Analysis System (Minitab .17) software and the significance of difference between means was determined by Tuky test. Result and discussions The results showed that the leaf area of chickpea was significantly affected by the test factors and their interactions. A 35%-increase in leaf area was observed at the lowest level of irrigation after exposure to 20 mg/L of TiO2-NPs. Chlorophyll index of chickpea was significantly affected by the test factors and their interactions. The interaction of two test factors showed that with an increase in the concentration of TiO2-NPs to 20 mg/L, chlorophyll index of chickpea was increased in all levels of irrigation. At all levels of irrigation, using the concentration of 40 mg/L of TiO2-NPs, the chlorophyll index in chickpea leaves were reduced compared to the concentration of 20 mg/L. The highest osmotic potential was observed in 40% capacity after treatment with 5 and 10 mg/L titanium dioxide nanoparticles. There were no significant differences between 40 and 20 mg/L at this level of irrigation. At all irrigation levels, the application of the nanoparticle produced the highest osmotic potential, and thus, the use of nanoparticles increases the osmotic potential compared to control plants. Osmotic regulation under the water shortage conditions decreases cellular inflammation by maintaining water and collecting material in the cell. Also, the percentage of dry weight of the whole chickpea plants was significantly affected by the test factors and their interactions. The interaction of two factors showed that with the increasing concentration of TiO2-NPs to 20 mg/L, the dry weight of chickpea in the lowest irrigation level was increased by10% compared to control plants. Stomatal conductivity in all irrigation levels had an upward trend by using TiO2-NPs. Conclusion Generally, TiO2-NPs showed a positive effect on the total dry and fresh weight of the whole chickpea plants. The application of 20 mg/L TiO2-NPs at all levels of irrigation reduced drought stress and prevented further plant losses. The application of low concentration of nanoparticles promoted plant growth and at high levels showed inhibitory effects on growth. Taken all together, due to the increasing use of chemical fertilizers in agriculture, nano compounds can be used as an appropriate alternative that increases product quality.